Facing Acromegaly During Rhinoplasty Procedure. Issue 7 (October 2021) - Dissaux, Caroline; Bruant-Rodier, Catherine; Ruffenach, Laetitia
Abstract : Abstract: Acromegaly is a rare pathology linked to a pituitary adenoma responsible for excessive secretions of growth hormone and insulin growth factor 1 inducing an overgrowth of most tissues, especially those which are visible in the face. Main problem stands in the usual delayed diagnosis. The authors report the case of a patient operated twice of a rhinoplasty before and after the acromegaly diagnosis for a very excessive nose. They emphasize the technical difficulties to efficiently reduce all the nasal dimensions, the importance of the soft tissues quality, as they cover the nasal cartilaginous framework, and the absolute necessity of biological normalization to provide a stable and satisfactory result. Abstract : Supplemental Digital Content is available in the text